Deacon King Kong - McBride, James, 1957- (Riverhead Books, 2020)
"From James McBride, author of the National Book Award-winning The Good Lord Bird, comes a wise and witty novel about what happens to the witnesses of a shooting. In September 1969, a fumbling, cranky old church deacon known as Sportcoat shuffles into the courtyard of the Cause Houses housing project in south Brooklyn, pulls a .45 from his pocket, and in front of everybody shoots the project's drug dealer at point-blank range. The reasons for this desperate burst of violence and the consequences that spring from it lie at the heart of Deacon King Kong, James McBride's funny, moving novel and his first since his National Book Award-winning The Good Lord Bird. In Deacon King Kong, McBride brings to vivid life the people affected by the shooting: the victim, the African-American and Latinx residents who witnessed it, the white neighbors, the local cops assigned to investigate, the members of the Five Ends Baptist Church where Sportcoat was deacon, the neighborhood's Italian mobsters, and Sportcoat himself. As the story deepens, it becomes clear that the lives of the characters--caught in the tumultuous swirl of 1960s New York--overlap in unexpected ways. When the truth does emerge, McBride shows us that not all secrets are meant to be hidden, that the best way to grow is to face change without fear, and that the seeds of love lie in hope and compassion. Bringing to these pages both his masterly storytelling skills and his abiding faith in humanity, James McBride has written a novel every bit as involving as The Good Lord Bird and as emotionally honest as The Color of Water. Told with insight and wit, Deacon King Kong demonstrates that love and faith live in all of us"--